Predictions of New Neutron-Rich Isotopes at N = 126 in the Multinucleon Transfer Reaction 136Xe + 194Ir - Jiang, Xiang; Wang, Nan (Frontiers in Physics, 2020)
Aiming to produce new neutron-rich nuclei around N=126, the multi-nucleon transfer reaction ^136Xe+^194Ir is investigated by using the GRAZING model and the three-dimensional time-dependent Hartree-Fock (TDHF) approach. De-excitation processes of the primary fragments are taken into account in both models. The results of GRAZING indicate that this system is a promising candidate for producing new neutron-rich isotones with N=126. In contrast, no such nuclei are observed in TDHF. Nucleon transfer process in TDHF collisions is studied and the relation to final isotopic production cross sections is discussed.